Students’ Stress and Loneliness During the COVID-19 Period - Hasmujaj, Elona; Andersons, Aigars; Bushati, Jozef (Pedagogika, 2024)
This study investigated stress and loneliness among students at the University of Shkoder, Albania, during COVID-19, finding higher stress among females and increased loneliness in social sciences students. It highlighted a significant correlation between stress and loneliness, suggesting implications for student health interventions and further research.